Factors Influencing Hospital Nurses’ Performance in Relation to Clinical Authority: A Literature Review - Arief Yanto; Menik Kustriyani (Universitas Muhammadiyah Semarang, 2025)
Hospital nurses’ performance within their clinical authority is essential for patient safety and care quality. Evidence from studies published between 2021 and 2025 indicates that performance is shaped by interactions between organizational, individual, and environmental factors rather than individual competence alone. This literature review synthesized empirical qualitative, quantitative, and mixed-methods studies examining determinants of nurses’ performance, including leadership, workload, empowerment, and work environment. Articles were systematically searched, screened, and thematically analyzed. Four key determinants emerged: supportive clinical leadership as the most influential factor; manageable workloads that reduce role conflict in clinical practice; structural empowerment and professional autonomy that encourage innovative behavior; and a positive organizational or team climate that supports collaboration. Major barriers included hierarchical organizational cultures, resource limitations, and lack of mentorship. Environmental considerations were frequently deprioritized due to time pressure and insufficient institutional support. Overall, nurses’ performance within their clinical authority is governed by a complex interplay of leadership, workload, empowerment, and organizational climate. Targeted organizational strategies and further research in diverse healthcare contexts are required to optimize nursing performance and maintain high-quality patient care.